OP0018 The value of adding mri to a clinical treat-to-target strategy in rheumatoid arthritis patients in clinical remission: clinical and radiographic outcomes from the imagine-ra randomised controlled trial. (12th June 2018) - Møller-Bisgaard, S.; Hørslev-Pedersen, K.; Ejbjerg, B.; Hetland, M.; Ørnbjerg, L.; Glinatsi, D.; Møller, J.; Boesen, M.; Christensen, R.; Stengaard-Pedersen, K.; Madsen, O.R.; Jensen, B.; et al.
Abstract : Background: Targeting MRI remission in rheumatoid arthritis (RA) patients in clinical remission may improve clinical outcome and halt joint damage progression. Objectives: To determine whether a treat-to-target (T2T) strategy based on structured MRI assessments targeting absence of osteitis/bone marrow oedema (BME) would lead to improved clinical and radiographic outcomes, compared with a conventional T2T strategy in RA patients in clinical remission. Methods: The IMAGINE-RA study was a 2 year investigator-initiated, randomised, open-label multicentre study. Two hundred RA patients in clinical remission (defined as: DAS28-CRP<3.2 and no swollen joints) receiving conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) were randomly assigned 1:1 to a conventional DAS28-CRP guided T2T strategy, targeting DAS28-CRP<3.2 and no swollen joints or an MRI guided T2T strategy based on the same clinical T2T strategy and MRI targeting absence of BME. Patients were followed every 4 months over a 2 year follow-up period. In the MRI T2T arm contrast-enhanced MRI of the dominant hand 2nd-5th metacarpophalangeal joints and wrist was performed ahead of the clinical visit and evaluated for presence/absence of BME. Treatment was escalated according to a predefined treatment algorithm if target was not reached, starting with increments in csDMARD mono/combination therapy and then adding biologic DMARDs. The co-primary endpoints were 1) proportion of patients achieving DAS28-CRP remission (DAS28-CRP<2.6) and 2) proportion of patients with no radiographic progression (change in total Sharp/vdHeijde score ≤0) 24 months from baseline. Secondary outcomes included various clinical, functional, radiographic and MRI variables. Pearson's chi-square statistics and repeated-measures logistic regression models were used to assess primary and secondary outcomes. Results: Primary and secondary clinical and radiographic outcomes at 24 months are presented in the table 1. 76 patients in the MRI T2T arm and 95 patients in conventional T2T arm completed the study. Of them 64 patients (85%) in the MRI T2T arm and 83 patients (88%) in the conventional T2T arm reached the primary clinical endpoint (chi-square=0.324, p=0.569) and 49 patients (66%) in the MRI T2T arm and 58 (62%) in the conventional T2T arm reached the primary radiographic endpoint (chi-square=0.265, p=0.606). ACR/EULAR remission rates, swollen joint count, patient VAS global and HAQ favoured the MRI T2T arm (p<0.038). Conclusions: Targeting absence of MRI BME in addition to a conventional T2T strategy in RA patients in clinical remission had no effect on the probability of achieving DAS28-CRP remission or halt radiographic progression. However, more patients achieved ACR/EULAR remission and improvements in physical function when MRI was used for treatment guidance. Clinicaltrials.gov Identifier: NCT01656278 Disclosure of Interest: None declared